REHABILITATION ACTIVITY OF FAMILIES AS AN EFFICIENCY CRITERION OF THE MEDICAL AND SOCIAL ASSISTANCE TO THE DISABLED CHILDREN - S.A. Kosova; A.A. Modestov; L.S. Namazova (Union of pediatricians of Russia, 2007)
Rehabilitation of the physically handicapped children requires interdepartmental integration. The most concerned link carrying on the interdepartmental integration may prove to be the family of a disabled child. The parents should have an opportunity and incentives to acquire specific skills to bring up a child and take care of them, since the rehabilitation of the physically handicapped children is a lengthy process and has some distinctive peculiarities at various age stages.Key words: rehabilitation, disabled children.